Class IA Phosphatidylinositol 3-Kinase Isoform p110α Mediates Vascular Remodeling. Issue 6 (June 2015) - Vantler, Marius; Jesus, Joana; Leppänen, Olli; Scherner, Maximilian; Berghausen, Eva Maria; Mustafov, Lenard; Chen, Xin; Kramer, Tilmann; Zierden, Mario; Gerhardt, Maximilian; ten Freyhaus, Henrik; Blaschke, Florian; et al.
Abstract : Objective—: Neointima formation after vascular injury remains a significant problem in clinical cardiology, and current preventive strategies are suboptimal. Phosphatidylinositol 3′-kinase is a central downstream mediator of growth factor signaling, but the role of phosphatidylinositol 3′-kinase isoforms in vascular remodeling remains elusive. We sought to systematically characterize the precise role of catalytic class IA phosphatidylinositol 3′-kinase isoforms (p110α, p110β, p110δ), which signal downstream of receptor tyrosine kinases, for vascular remodeling in vivo. Approach and Results—: Western blot analyses revealed that all 3 isoforms are abundantly expressed in smooth muscle cells. To analyze their significance for receptor tyrosine kinases–dependent cellular responses, we used targeted gene knockdown and isoform-specific small molecule inhibitors of p110α (PIK-75), p110β (TGX-221), and p110δ (IC-87114), respectively. We identified p110α to be crucial for receptor tyrosine kinases signaling, thus affecting proliferation, migration, and survival of rat, murine, and human smooth muscle cells, whereas p110β and p110δ activities were dispensable. Surprisingly, p110δ exerted noncatalytic functions in smooth muscle cell proliferation, but had no effect on migration. Based on these results, we generated a mouse model of smooth muscle cell–specific p110α deficiency (sm-p110α −/− ). Targeted deletion of p110α in sm-p110α −/− mice blunted growth factor–induced cellular responses and abolished neointima formation after balloon injury of the carotid artery in mice. In contrast, p110δ deficiency did not affect vascular remodeling in vivo. Conclusions—: Receptor tyrosine kinases–induced phosphatidylinositol 3′-kinase signaling via the p110α isoform plays a central role for vascular remodeling in vivo. Thus, p110α represents a selective target for the prevention of neointima formation after vascular injury, whereas p110β and p110δ expression and activity do not play a significant role. Abstract : Supplemental Digital Content is available in the text.